Determination of Soil Erodibility (K) Factor Derived from Different Geologic Formations of Akwa Ibom State (Nigerian Journal of Technology, 2021)
The onsite and offsite effect of erosion has caused it to be considered as a global issue. For erosion to occur there must be soil erodibility and rainfall erosivity. Different geologic formations give rise to different types of soil and this has affect their responses to an erosive event. Five (5) geologic formations were identified within the study area. This study assessed the erodibility of soils from different geologic formations. Soil samples were taken at a depth of 0-10, 10-20, 20-30 cm for standard laboratory analysis. The fine sand, silt, clay, organic matter and permeability of the soils obtained from the different geologic formations were used to determine their erodibility indices using Wischmeier and Smith model. The results obtained shows that Alluvium geologic formation has an average K factor of 0.150 tons MJ-1 hmm-1. Ameki had an average K factor of 0.131 MJmmha-1hr-1yr. Benin had an average K factor of 0.130 tons MJ-1 hmm-1. Imo had an average K factor of 0.147 tons MJ-1 hmm-1. Ogwashi had an average K factor K of 0.127 tons MJ-1 hmm-1. The results show that soils within the study area are vulnerable to erosion.